Molecular epidemiology and antiviral resistance characterization of Hepatitis C virus circulating in Africa and Brazil - Adeboyejo, Kazeem Adeyinka (2020)
Hepatitis C virus (HCV) infection is a public health problem that is responsible for liver disease and hepatocellular carcinoma Worldwide. Remarkable achievements have been made in the study of molecular epidemiology of HCV in industrialized countries, and this information is proving invaluable in the design of appropriate HCV antiviral treatments. However, throughout sub-Saharan Africa, the understanding and knowledge of the prevalence and distribution of HCV genotypes and subtypes is woefully inadequate, and those studies that do exist have often utilised unreliable commercially available subtyping assays. In this study, we utilised serum samples drawn from 135 patients enrolled in the HCV Research UK cohort to delineate the molecular epidemiology of HCV in 32 countries situated across Africa. We used a Sanger population sequencing approach to define genetic diversity and resistance associated substitutions of HCV sequence. Subtyping was performed using the NS5B and NS5A phylogenetic analyses, which were then compared to results generated using a variety of on-line resistance-associated substitution (RAS) and subtyping tools as well as clinic data that had been generated using commercially available assays. The study revealed the presence of diverse subtypes within the study cohort, many of which harboured naturally occurring RAS. While the online tools performed reasonably well in terms of RAS and subtype prediction, phylogenetic analysis proved to be the most robust method. Critically, the commercial genotyping assays could not accurately subtype or genotype a large proportion of the HCV sequences. In order to develop a subtyping/RAS analysis procedure suitable for resource-poor settings, we also investigated the use of dried serum spot (DSS) sampling for molecular epidemiological studies. Using serum samples collected in Brazil, we showed that this system was suitable for the collection, shipping, and processing of samples that were then suitable for downstream molecular epidemiological studies.